(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
درسنا في هذا البحث إحدى مسائل التحليل التابعي وهي مسألة تداخل الفضاءات التابعية، وبشكل خاص فقد درسنا تداخل الفضاءات المتعلقة بفضاءات هولدر. كما درسنا التداخل لفضاءات والذي يعتمد في تعريفه على فضاءات أورليتش وفضاءات ليبيغ ويعتبر في حالة خاصة تعميماً لهما. We study in this research one of the functional analysis problems,it is the inclusion of functional spaces. Especially we study the inclusion of spaces which branched form Holder spaces. Alsowe study the inclusion of spaces whichdepends in it definition onOrlicz and Lebesgue spaces and in anespecial case this space is generalization to them.